Wall ceramic deco arts as theraphy / Megat Amirul Ashraf Megat Zambri, Md Faizul Khalid @ Abd Malek and Mohamad Akmal Daros - Megat Zambri, Megat Amirul Ashraf; Khalid @ Abd Malek, Md Faizul; Daros, Mohamad Akmal (Research Innovation Business Unit, 2014)
The ‘wall ceramic deco’ is produced because it is compatible with the concept of interior decoration currently looking for a simple deco and urban nature in which this artwork fills the walls as decoration. In addition, it can be used as a therapy for the mind for those who love flora and fauna. ‘Wall ceramic decor’ is produced through a process of ceramic production, where the production of this art work is custom made. Emphasis is given to the decoration on the ceramic surface in detail, using soft colours and also creating some texture for contrast will portray a big impact on the art work. Other than that it is important to give awareness about nature towards human, in addition to promoting the use of ceramic for interior decoration to create space and beauty of the scenery on the wall. Technique used to create the plate is a throwing technique and mix with hand build technique. Colours also create the mood. For the decorating the surface the design is more focussed on the elements and principle of design such as lines. The shape of the wall is more to focus on basic forms. It is because urban concepts are more simple shapes.